Intuitive intelligence for individuals - Subiah, Manj (Henry Stewart Talks, 2020)
How to develop as a leader, Four precepts of intuitive intelligence, VUCA (Volatile, Uncertain, Complex, Ambiguous), Intuitive intelligence model™